1998
DOI: 10.1007/bf02467712
|View full text |Cite
|
Sign up to set email alerts
|

Ion-exchange chromatography with an oxalic acid-α-hydroxyisobutyric acid eluent for the separation and quantitation of rare-earth elements in monazite and xenotime

Abstract: Key WordsColumn liquid chromatography Ion-exchange Rare-earth elements Monazite Xenotime SummaryAn oxalic acid-c~-hydroxyisobutyric acid eluent has been used for the separation and determination of rareearth elements by high-performance ion-exchange chromatography. Fifteen rare-earth elements were separated within less than 25 rain on a 150 • 4.6 mm i.d. column packed with 5-1am sulfonic acid-bonded silica particles by elution with a combined gradient of 0.60-9.0 mM oxalic acid and 19.0-5.0 mM ot-hydroxyisobut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 26 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Fernández and Alonso [20] recently used ethylenediaminetetraacetic acid (EDTA) as a mobile phase in the separation of lanthanides. A mixed gradient of two eluents has also been used in some researches [13,21]. The most popular eluting agent in these works is HIBA due to a good degree of separation among adjacent lanthanides.…”
Section: Introductionmentioning
confidence: 99%
“…Fernández and Alonso [20] recently used ethylenediaminetetraacetic acid (EDTA) as a mobile phase in the separation of lanthanides. A mixed gradient of two eluents has also been used in some researches [13,21]. The most popular eluting agent in these works is HIBA due to a good degree of separation among adjacent lanthanides.…”
Section: Introductionmentioning
confidence: 99%
“…A 2 M stock solution of HIBA was adjusted to pH 4.6 using ultrapure NH 4 OH (Merck). Nuryono et al (1998) showed that the elution time and resolution during HIBA column chromatography depended on the pH of HIBA. Therefore, the authors recommended that pH 4.6 is optimal for REE separation by HIBA column chromatography because at pH < 4.6, the eluent is too weak to elute REE ions and at pH > 4.6, the resolution is too low to guarantee adequate REE separation.…”
Section: Introductionmentioning
confidence: 99%